Pemodelan Proses Bisnis Kuliah Online MOOCs menggunakan BPMN (Studi Kasus alison.com) - Sumarsono Sumarsono; Dodi Saputro; Aulia Faqih Rifai (JISKA (Jurnal Informatika Sunan Kalijaga), 2023)
Online lectures have been recognized for their existence in independent learning. However, many still don't know the scope of the business process, from the account registration process to taking exams. This article discusses business process modeling using Business Process Modeling Notation (BPMN) in online lectures on the international standard ALISON MOOC models. This research aims to overview the process and business model of MOOC online lectures with ALISON. This type of research is descriptive qualitative, which describes objective conditions based on facts the researcher found in the field. Data is collected through literature study, problem analysis, and business process modeling. This research results in modeling the online college business process at ALISON. The business process elements, from course registration to the exam implementation, are mapped in detail using the BPMN standard. Through modeling using BPMN, the process of creating an account, participant profile, course selection, course registration, learning media, completing assignments and exams, and obtaining a certificate can be described. This article provides helpful information for users interested in business process modeling and its notation in the ALISON online course.